Maturity assessment of knowledge management at noc departement of pt. Huwaei services - Adi Nuryono, Wahyu; J. Susilo, Leo (The Indonesian Journal of Business Administration, 2019)
Abstract. Indonesia is the largest archipelagic country with a total population of 259 million. The growth of telecommunication and technology users is increase every year. At the same time, telecommunications companies in Indonesia are trying to be the best in providing services to their users. The operators are always innovating in providing services, and to achieve this, telecommunication operators are very selective in cooperating with second parties, in this case telecommunications vendors. PT Huawei Services is one of the largest telecommunication service providers in Indonesia. PT Huawei services is a transformation of PT XL Axiata's service management. This transformation from operators to telecommunications vendors is making changes in work culture and work environment. In this transformation process, some employees choose to quit the company and result in a reduction in employees who have high work experience. This has an effect on knowledge management at PT Huawei services. The volume of sharing sessions every week starts to decrease and almost nothing. In this study, researchers tried to measure the level of maturity of knowledge management in PT Huawei services, especially at the NOC department. The method used in this research is qualitative and quantitative methods. Qualitative methods are conducted by interviewing the management of PT Huawei Services. And the quantitative method is by conducting a survey of company employees. From the qualitative and quantitative method, researcher can conclude that the company at Defined level, it is mean knowledge management is already implemented and deployed in the company but there are still need an improvement in several aspects. The company are focusing on how to make standard in KM initiative.Keywords:  knowledge, Knowledge Management, Telecommunication, Manage service, KM maturity